"Caffeine Doping" of Carbon/Nitrogen‐Based Organic Catalysts: Caffeine as a Supramolecular Edge Modifier for the Synthesis of Photoactive Carbon Nitride Tubes. Issue 18 (24th June 2015) - Jordan, Thomas; Fechler, Nina; Xu, Jingsan; Brenner, Thomas J. K.; Antonietti, Markus; Shalom, Menny
Abstract An alternative method for the structure tuning of carbon nitride materials by using a supramolecular approach in combination with caffeine as lining‐agent is described. The self‐assembly of the precursor complex consisting of melamine and cyanuric acid can be controlled by this doping molecule in terms of morphology, electronic, and photophysical properties. Caffeine is proposed to insert as an edge‐molecule eventually leading to hollow tube‐like carbon nitride structures with improved efficiency of charge formation. Compared to the bulk carbon nitride, the caffeine‐doped analogue possesses a higher photocatalytic activity for the degradation of rhodamine B dye. Furthermore, this approach is also shown to be suitable for the modification of carbon nitride electrodes.